Malaysia’s Governance Reforms under PM Najib Razak - Endi Haryono (AEGIS : Journal of International Relations, 2017)
In response to new socio-political conditions in Malaysia following the general election, Prime Minister Najib Tun Razak launched a reform that brought fundamental changes in the economy and governance in Malaysia. By the end of 2011, there were four reform programs - TNR called it a transformation - covering three programs in the first two years of its administration, namely the introduction of the One Malaysia Concept (1Malaysia), the Government Transformation Program (GTP), and the New Economic Model Model / NEM). Entering the third year (2011) Najib fulfilled it with political reform, including the abolition of the Domestic Security Act (ISA). Reforms are an inescapable choice and an option that is not easy in order to maintain popular support for the Barisan Nasional (BN) coalition, especially the United Malay National Organization (UMNO), which is ruling.